Interaksi Interaksi Iklim Sekolah, Inovasi Guru, dan Ketekunan Akademik dalam Meningkatkan Prestasi Kimia: Pendekatan Pemodelan Persamaan Struktural - Abukasim, Sudarto; Sutrisno, Hari; Rohaeti, Eli (Jurnal Pendidikan Indonesia, 2025)
This study was motivated by the low level of student's understanding of complex chemical concepts, which is the main challenge in learning chemistry at the high school level. The primary objective of this study was to investigate the impact of academic persistence, teacher innovation, and school climate on the cognitive achievement of high school students in chemistry learning. This study employed a non-experimental, quantitative approach using Structural Equation Modeling (SEM). The study subjects consisted of 1,057 high school students in North Maluku Province. Data were collected through a questionnaire that included 26 items for cognitive achievement, 10 items for academic persistence, and instruments to measure teacher innovation and school climate. Data analysis was conducted using structural equation modeling (SEM) to examine the relationship between variables. The results showed that academic persistence had a significant effect on students' cognitive achievement (P-value = 0.659). Teacher innovation also had a significant positive effect (P-value = 0.634), while school climate did not show a significant effect. Academic persistence has been proven to be the primary predictor of students' commitment and resilience in facing learning challenges. This finding also highlights the importance of teacher innovation, particularly in the application of technology-based and interactive learning methods, in enhancing student learning outcomes. The implications of this study underscore the need for strategies that enhance chemistry learning, focusing on strengthening student character and promoting pedagogical innovation. Further research is recommended to refine the model by incorporating additional variables to enhance chemistry learning in schools.